Effects of Divalent Metal Cations and Resistance Mechanisms of the Cyanobacterium Synechococcus SP. Strain PCC 7942 - G. R. Ybarra; R. Webb (Journal of Hazardous Substance Research, 1999)
Cyanobacteria exhibit an extraordinary resistance to many environmental factors including nutrient limitation, changes in hydrogen ion concentration, temperature, and light extremes. A better understanding of the biological effects and response mechanisms of cyanobacteria to heavy metal exposure could be used to develop these bacteria for use in bioremediation. Synechococcus sp. strain PCC 7942 expresses messenger RNA for the stress protein GroEL and for the metal-binding protein metallothionein in response to a wide range of divalent metal ion concentrations. Although groEL is expressed at low levels regardless of environmental conditions, a high rate of transcription is initiated within 15 minutes following exposure to divalent metal cations at concentrations ranging from 10 µM to 100 µM for copper and zinc, and concentrations as low as 1 µM for cadmium. Transcript levels return to normal within one hour following exposure to each metal. Induction of the metallothionein operon also occurs within 15 minutes of these exposures. We speculate that these resistance mechanisms are working together to protect the cell from damage.
Keywords: metallothionein; GroEL; cyanobacteria; resistance mechanisms